A cross-country utilization patterns comparison of high expenditure therapeutic groups between Portugal and six European countries: the two sides of the Portuguese coin. (2nd January 2023) - Martinho, Inês; Teixeira Rodrigues, António; Guerreiro, José; Rocha, João; Sepodes, Bruno; Torre, Carla
ABSTRACT: Background: Understanding variability in prescribing patterns through comparative drug utilization studies can contribute to improve an efficient, effective and safe use of medicines. Objectives: To perform a cross-country comparison of consumption patterns of ambulatory high expenditure therapeutic groups between Portugal and six European countries and simulate potential cost-saving scenarios through the adoption of the different prescribing patterns of studied countries. Methods: Cross-country comparison of 2019 drug consumption patterns between Portugal, Denmark, England, Finland, the Netherlands, Norway, and Spain. Analysis comprised antihypertensive drugs, glucose lowering drugs (GLD), insulins, lipid lowering drugs (LLD) and oral anticoagulants. Cost-saving analysis were performed using the Portugal average annual cost/daily defined dose and the potential reduction in expenditure simulating other European countries consumption pattern scenarios. Results: Portugal had the lowest consumption uptake of metformin and the highest consumption of GLD (30.1%) and LLD (8.5% vs <3%) fixed-dose combinations. Annual cost-savings scenarios showed that Portugal would have saved between 53 M€ and 305 M€ if it had the same prescribing patterns than Norway or the Netherlands, respectively. Conclusions: Different utilization patterns across countries were found. Although Portugal has the lowest gross domestic product per capita among the countries studied, it had the highest uptake of newly and costly drugs.